Isatin derivatives as a non-toxic corrosion inhibitor for mild steel in 20% H2SO4 - Ansari K.R.; Quraishi M.A.; Singh A. (My University, 2025)
The corrosion inhibition action of Isatin-β-thiosemicarbzone derivatives namely 1-Benzylidene-5-(2-oxoindoline-3-ylidene) Thiocarbohydrazone (TZ-1) and 1-(4-Methylbenzylidene)-5-(2-oxoindolin-3-ylidene) Thiocarbohydrazone (TZ-2) was studied on mild steel surface in 20% H2SO4 by gravimetric measurements, Electrochemical measurements (EIS and Tafel), SEM, EDX and quantum chemical methods. Potentiodynamic polarization curves reveal that the TZs act as mixed type inhibitors exhibiting predominantly cathodic behavior. The adsorption of TZs obeys the Langmuir adsorption isotherm. The thermodynamic parameters (Ea, Kads, δG°ads) were also computed and discussed. © 2015 Elsevier Ltd.